Evaluating population estimates of mountain goats based on citizen science - Jami J. Belt; Paul R. Krausman (Wildlife Society Bulletin)
Abstract Citizen science programs that use trained volunteers may be a cost‐effective method for monitoring wildlife at large scales. However, few studies have compared data collected by volunteers versus biologists. In Glacier National Park (GNP), Montana, USA, we assessed whether citizen science is a useful method to monitor mountain goat (Oreamnos americanus) populations. We compared estimates of mountain goat abundance by volunteers at 32 sites throughout GNP with estimates by biologists and aerial surveys at a subset of 25 and 11 sites, respectively. We used multiple‐observer surveys to calibrate the indices of abundance at each site for observer variation between volunteers and biologists. We used N‐mixture models to obtain estimates of abundance across all sites. Population estimates by citizen scientists overlapped estimates by biologists. Density estimates from aerial surveys were lower than ground estimates. Mean detection probability from multiple‐observer surveys for biologists was significantly higher and less variable than that of volunteers. More frequent site visits balanced out lower detection probability by volunteers and resulted in abundance estimates that were less variable than those of biologists. When large spatial and temporal coverage can be achieved, citizen science can provide mountain goat population estimates that are statistically similar to those of biologists. © 2012 The Wildlife Society.